2022
DOI: 10.7759/cureus.27032
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use Reduces the Risk of Hepatocellular Carcinoma: An Updated Meta-Analysis and Systematic Review

Abstract: Hepatocellular carcinoma (HCC) is the most common primary tumor of the liver resulting in approximately 800,000 deaths annually. A growing body of research investigating statin use and HCC risk has shown conflicting results. We aim to evaluate the current evidence of statin impact on HCC risk.We performed a comprehensive literature search in PubMed, PubMed Central, Embase, and ScienceDirect databases from inception through May 2019 to identify all studies that evaluated the association between statin use and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(123 reference statements)
0
5
0
Order By: Relevance
“…Intriguingly but somehow disappointingly, indications from prospective interventional trials and studies remain inconclusive, although association of statin use with a decreased risk of HCC carcinogenesis and recurrence has been described ( Table 2 ) ( Chiu et al, 2011 ; Tsan et al, 2012 ; Butt et al, 2015 ; Kawaguchi et al, 2017 ; Khazaaleh et al, 2022 ). In virus-independent liver lesions, atorvastatin use (10 mg/day) in NASH patients indicated an improvement in liver functions by 74%, along with a rise in serum protein and lipid metabolism regulator adiponectin ( Hyogo et al, 2008 ; Athyros et al, 2017 ).…”
Section: Lipid-targeting Statins In Hccmentioning
confidence: 99%
“…Intriguingly but somehow disappointingly, indications from prospective interventional trials and studies remain inconclusive, although association of statin use with a decreased risk of HCC carcinogenesis and recurrence has been described ( Table 2 ) ( Chiu et al, 2011 ; Tsan et al, 2012 ; Butt et al, 2015 ; Kawaguchi et al, 2017 ; Khazaaleh et al, 2022 ). In virus-independent liver lesions, atorvastatin use (10 mg/day) in NASH patients indicated an improvement in liver functions by 74%, along with a rise in serum protein and lipid metabolism regulator adiponectin ( Hyogo et al, 2008 ; Athyros et al, 2017 ).…”
Section: Lipid-targeting Statins In Hccmentioning
confidence: 99%
“…Intriguingly but somehow disappointingly, indications from prospective interventional trials and studies remain inconclusive, although association of statin use with a decreased risk of HCC carcinogenesis and recurrence has been described (Table 2) (Chiu et al, 2011;Tsan et al, 2012;Butt et al, 2015;Kawaguchi et al, 2017;Khazaaleh et al, 2022). In virus-independent liver lesions, atorvastatin use (10 mg/day) in NASH patients indicated an improvement in liver functions by 74%, along with a rise in serum protein and lipid metabolism regulator adiponectin (Hyogo et al, 2008;Athyros et al, 2017).…”
Section: Monotherapy Use Of Statins In Hccmentioning
confidence: 99%
“…A meta-analysis of 20 studies and a total of 2,668,497 patients [100] evaluated the beneficial role of statins for HCC prevention (OR: 0.573; 95% CI: 0.491-0.668, I2 = 86.57%); the study included six cohort studies, four of which found a positive association between statin use and a significantly lower risk of HCC development. Eleven case-control studies have also established that statin use is beneficial in reducing the risk of HCC.…”
Section: Statins In Hcc Preventionmentioning
confidence: 99%